The Basic Stages of Preparing a Public Budget - Hamad Al-Hakeem, Mustafa; Ilham Abdal, Kahi (International Journal of Scientific Research and Management (IJSRM), 2019)
Budgeting is creating a plan to spend your money.  Good budgeting is spending less than you are earning as you plan for your financial goals.  Budgeting is the fundamental step in achieving financial literacy, and by extension, reaching financial security and freedom.  Budgeting is the process of creating a plan to spend and invest your hard earned money wisely to meet your personal and financial goals in life.  It should not be a mathematical exercise that we think we have to endure; rather, it is the result of self- assessment of our relationship with money and a necessary road map to steer us toward a higher standard and quality of living. The budget determines the general policy of the State and reflects its economic and development orientations and the partnership of all citizens with regard to their tax obligations or service rights. This is a strategic plan as a result of the expenditure study for years, taking into account the needs and potential of the ministries and the capacity to mobilize resources to cover the public expenditure of the State.